(untitled) (Metallurgy and Foundry Engineering, 2009)
Stereological description of dispersed microstructure is not an easy problem and is constantly a subject of research [1, 2]. From the practical point of view, the stereological description of this type of microstructures is essential in analyses of such processes as coarsening, spheroidization or in research of relationship between the microstructure and mechanical properties (e.g. bearing steel). The method of computer simulation is a very comfortable and effective way to test properties of stereological parameters of a microstructure. The computer model of a dispersed microstructure presented in the work is based on the following assumptions: (1) particles of dispersed phase are spheres randomly distributed in space; the input data are: number of spheres in unit volume Nv, volume fraction of spheres Vv and distribution of sphere diameters in space (through the probability density function f(D)), (2) the system of spheres is being cut by the cutting planes. As a result of the simulation we obtain the distributions of flat sections’ diameters. The correctness of the model performance has been verified considering two cases relating to which we know analytical relations between distribution of spheres in space and distributions of flat sections’ diameters: (1) the simulated structure consists of spheres of equal size, (2) spheres are subject to the Rayleigh distribution.